(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
From the legal lexicon on family relationships made possible by procreative techniques, the terms sexuality, motherhood and fatherhood have disappeared, replaced by affectivity and parenting. The paper traces these semantic options to the choice of approaching the phenomenon solely through the homologizing logics of anti-discrimination law and suggests a perspective that, eschewing reductive readings of Article 3 Const. does not irenically devalue sexual difference in the name of a neutral social parent.